ANÁLISE DO USO DE ARMADILHAS COM ISCAS PARA CAPTURA DE ONISCIDEA (CRUSTACEA: ISOPODA) EM MATA ESTACIONAL SEMIDECIDUAL EM DOURADOS/MS - SOUZA, Gabriel Gomes Rodrigues; NAKAGAKI, Jelly Makoto; OLIVEIRA, Welinton Lima (ANAIS DO ENIC, 2020)
-